ROLE OF LYCOPENE IN PREVENTING PROSTATE CANCER - Made Tami Budirejeki; I Wayan Sugiritama (Universitas Udayana, 2013)
Prostate cancer is the most common male cancer in the United States in 2003. Prostate cancer is the second cause of death after lung cancer. The possibility of a man suffering from prostate cancer is about 3 %. Increasing age is the main risk factor for this disease. Eighty percent of prostate cancer patients aged over 65 years. Prostate cancer occurs due to accumulation of DNA damage. There are various mechanisms that cause DNA damage, one of them is due to oxidative stress. Imbalance levels of free radicals and antioxidant in tissues causes oxidative stress. Antioxidants are substance that has ability to neutralize free radicals. One of the powerful antioxidant is lycopene. It is belived have ability to prevent prostate cancer. Various studies and reviews have been conducted to determine the role of lycopene in the prevention of prostate cancer. Although most studies have found an association between the consumption of foods that contain lycopene with a reduced risk of prostate cancer, but few studies have found no such relationship.